Feasibility of SWBSEA Application In Learning At Istiqlal Senior High School - Ningrum, Dita Dwi; Siregar, Alkhafi Maas (Journal of Learning and Technology in Physics, 2020)
Practical methods are very rarely used in learning physics so that Students have difficulty understanding concepts. Student Worksheets are needed to support practical work. Student Worksheets used in learning are not feasible. Fulfillment of the feasibility test in learning in this study is intended to test and determine the level of feasibility of Student Worksheets Based on the Starter Experiment Approach (SWBSEA). The design of the SWBSEA is based on curriculum needs, Student knowledge, and Student skills. Testing the level of feasibility and application of SWBSEA is given to Students during learning and submits a questionnaire to assess the feasibility of use. The results showed that SWBSEA in Physics learning was considered feasible in terms of Content Display, Subject Display, Component Completeness, and Grammar.